POLA REKRUTMEN CALON LEGISLATIF DAPIL 1 PROVINSI ACEH YANG DILAKUKAN OLEH PARTAI KEADILAN SEJAHTERA (PKS) DAN PARTAI NASIONAL DEMOKRAT (NASDEM) - Ruslan Ruslan; Yusrijal Abdar (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2016)
Political recruitment is the process of filling positions in political institutions, including political parties. While the Political Party is a vehicle to bring a particular party political interests in the throne of power in order to achieve what is expected. The purpose of this research is to see how the pattern of recruiting candidates for legislative constituency 1 Aceh province conducted by PKS and NasDem Party, criteria to be used in recruiting candidates for legislative constituency 1 Aceh province conducted by PKS and NasDem Party and what the opportunities and challenges in recruiting candidates one electoral district conducted by PKS and NasDem Party. The method used is descriptive method with qualitative approach. The data collection was done by interview and documentation. The result showed that the pattern of recruiting candidates for the electoral district legilatif 1 Aceh province conducted by the PKS and NasDem show that much different. In connection with this, it is an opportunity and a challenge PKS namely the legislative elections of 2014 more challenges than opportunities obtained by the PKS because of money politics so were experienced by the Party NasDem money politics becomes the greatest challenge in the legislative election first times followed by the Party NasDem